First insight to the Finnish nationwide electronic prescription database as a data source for pharmacoepidemiology research - Aarnio E.; Huupponen R.; Martikainen J.; Korhonen M. (Elsevier Inc., 2025)
Background: Since 1994, the Finnish Prescription Register (FPR) has been the main data source for pharmacoepidemiology research in Finland. However, the FPR data are limited to reimbursed dispensations only. Implementation of electronic prescribing started in 2010 and after a stepwise extension, electronic prescribing became mandatory in all healthcare settings in 2017. Prescriptions issued and dispensed electronically are stored in the Prescription Centre of the nationwide Kanta database.
Objectives: To describe the contents of the Kanta database and to compare the coverage of Kanta with the FPR, using prescriptions and dispensations of oral anticoagulants (OACs) as an example.
Methods: All prescriptions, dispensations, and their cancellations and corrections for OACs recorded in Kanta were retrieved for the period 2012–2016.
Results: In 2016, the total number of valid electronic prescriptions for OACs was 249 139 and the number of valid electronic OAC dispensations was 765 745. The number of identified direct oral anticoagulant (DOAC) users was higher in Kanta compared to the FPR since 2014, although more users of all OACs were identified from the FPR during 2012–2015. In 2016, an indication was identified in 44.7% of OAC prescriptions and dosing instructions in 99.5% of DOAC prescriptions.
Conclusions: The Kanta database is a promising source of data on medication exposure. Because of reimbursement restrictions, use of DOACs was under-ascertained through the FPR.